Injury trends in sanctioned mixed martial arts competition: a 5-year review from 2002 to 2007. Issue 8 (28th February 2008) - Ngai, K M; Levy, F; Hsu, E B
Abstract : Background: Professional mixed martial arts (MMA) competition is a full-contact sport that has risen rapidly in popularity in recent years. However, there is limited information regarding the incidence of competition injuries after sanctioning by an athletic commission. Methods: We conducted a retrospective cohort study to examine MMA injury patterns during a 5 year period after sanctioning in the state of Nevada. Data from all regulated MMA competitions during the study period from March 2002 to September 2007 (1270 fight exposures) was obtained. Injury odds ratios were calculated by conditional logistic regression on match outcome, age, weight, and fight experience, using a pair-matched case-control design (n = 464) and by multiple logistic regression on match outcome, age, fight experience, weight, combat minutes, and scheduled rounds. Results: During the 635 professional MMA matches, 300 of the 1270 athletes sustained documented injuries with an injury rate of 23.6 per 100 fight participations. Most common reported injuries were lacerations and upper limb injuries. Severe concussion rate was 15.4 per 1000 athlete exposures, or 3% of all matches. No deaths or critical sports-related injuries resulted from any of the regulated matches during the study period. Age, weight and fight experience did not statistically increase the likelihood of injuries after controlling for other covariates. Conclusions: Injury rates in regulated professional MMA competition are similar to other combat sports; the overall risk of critical sports-related injury seems to be low. Additional study is warranted to achieve a better understanding of injury trends and ways to further lower injury risk in MMA.